Risk factors for overweight and obesity in Mexican American children and adolescents living on the Texas–Mexico border - Low, Ee Vien; Lee, Miryoung; Bauer, Cici; Fisher-Hoch, Susan P.; McCormick, Joseph B.; Rowan, Paul J.; Abughosh, Susan; Essien, Ekere J.; Chen, Hua (Frontiers in Adolescent Medicine, 2024)
Background This study aimed to compare the obesity rates between border-residing Mexican American children with the National Health and Nutritional Surveys (NHANES), and to examine the individual and household characteristics associated with weight status in these children. Methods This was a cross-sectional analysis of 354 children aged 8–18 years and their parents in the Cameron County Hispanic Cohort (CCHC) from 2014 to 2020. Children were categorized as healthy weight, overweight, class 1 obesity, class 2 obesity and class 3 obesity. The distribution of CCHC children's weight status was compared with Hispanic participants of the NHANES with matched age, sex, and the year of the interview. An ordinal least square regression analysis was conducted to assess the association between individual and household characteristics with CCHC children's weight status. Results Approximately 48.0% of CCHC children had a healthy weight, 17.9% were overweight, 22.2% were in class 1 obesity, 7.7% were in class 2 obesity, and 4.3% were in category 3. The weight distribution of the CCHC cohort was similar to that in the matched NHANES participants (p = 0.28). Being overweight was associated with higher household income (OR = 2.25, 95% CI: 1.01–5.02) while being in class 2 and class 3 obesity was associated with boys (Class 2 & 3 obesity: OR = 2.94, 95% CI: 1.27–6.81) and environmental factors such as parents' BMI (Class 2 and3 Obesity: OR = 1.13, 95% CI: 1.05–1.21). Conclusions Family socioeconomic status was positively associated with being overweight and Class 1 obesity, while gender and parent's BMI affected a child's likelihood of being class 2 and 3 obesity.